Population dynamics of migrant wheat aphids in China’s main wheat production region and their interactions with bacterial symbionts - Li, Tong; Yang, Gongqiang; Li, Qian; Jiang, Yueli; Kang, Dongmei; Fan, Zhiye; Gong, Zhongjun; Lu, Ruijie; Zhou, Guotao; Wu, Yuqing; Lu, Chuantao (Frontiers in Plant Science, 2023)
Sitobion miscanthi, Rhopalosiphum padi, and Schizaphis graminum are the three main pests in Chinese wheat-producing regions. In 2020, they are classified into the Chinese Class I list of agricultural diseases and pests, due to their severe harm to wheat plantings. S. miscanthi, R. padi, and S. graminum are migrant pests, and understanding their migration patterns and simulating their migration trajectories would improve forecasting and controlling them. Furthermore, the bacterial community of the migrant wheat aphid is also less known. In this study, we employed a suction trap to uncover the migration patterns of the three wheat aphid species in Yuanyang county, Henan province, during 2018 to 2020. And then the migration trajectories of S. miscanthi and R. padi were simulated using the NOAA HYSPLIT model. The interactions between wheat aphids and bacteria were further revealed by specific PCR and 16S rRNA amplicon sequencing. The results showed that the population dynamics of migrant wheat aphids was varied. Most of the trapped samples were identified to be R. padi, and S. graminum was the least collected sample. Typically, R. padi had two migration peaks in the 3 years, whereas S. miscanthi and S. graminum only exhibited one migration peak in 2018 and 2019. Moreover, the aphid migration trajectories varied over the years. Generally, the aphids originated from the south and migrated to the north. Herein, the infections of three main aphid facultative bacterial symbionts, Serratia symbiotica, Hamiltonella defensa, and Regiella insercticola, were detected in S. miscanthi and R. padi with specific PCR. Rickettsiella, Arsenophonus, Rickettsia, and Wolbachia were further identified with 16S rRNA amplicon sequencing. Biomarker searching indicated that Arsenophonus was significantly enriched in R. padi. Furthermore, diversity analyses showed that the bacterial community of R. padi had a higher richness and evenness than that of S. miscanthi. In conclusion, this study expands our knowledge about the migration patterns of aphids in the main wheat plant region of China and reveals the interactions between bacterial symbionts and migrant aphids.